2018
DOI: 10.3390/ijms19113585
|View full text |Cite
|
Sign up to set email alerts
|

Potential Causes of Titanium Particle and Ion Release in Implant Dentistry: A Systematic Review

Abstract: Implant surface characteristics, as well as physical and mechanical properties, are responsible for the positive interaction between the dental implant, the bone and the surrounding soft tissues. Unfortunately, the dental implant surface does not remain unaltered and changes over time during the life of the implant. If changes occur at the implant surface, mucositis and peri-implantitis processes could be initiated; implant osseointegration might be disrupted and bone resorption phenomena (osteolysis) may lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(175 citation statements)
references
References 181 publications
(257 reference statements)
3
143
0
4
Order By: Relevance
“…Subsequently, recruited macrophages phagocytize some small CoCrMo particles, while foreign body multinucleated giant cells surround very large particles [44]. Inside the cells, the particles are exposed to oxidative attacks, and consequently, high levels of ions might be released during the chemical corrosion processes [45]. Therefore, CoCrMo particles not only have a destructive effect because of their physical properties-the corrosion process and the presence of metal ions can also cause some biological reactions in the surrounding tissues [46].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, recruited macrophages phagocytize some small CoCrMo particles, while foreign body multinucleated giant cells surround very large particles [44]. Inside the cells, the particles are exposed to oxidative attacks, and consequently, high levels of ions might be released during the chemical corrosion processes [45]. Therefore, CoCrMo particles not only have a destructive effect because of their physical properties-the corrosion process and the presence of metal ions can also cause some biological reactions in the surrounding tissues [46].…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews have confirmed the negative effect of implants degradation products on biological systems (Delgado-Ruiz and Romanos, 2018;Suárez-López Del Amo et al, 2018). In fact, weakened surfaces due to the bio-tribocorrosion process may release metallic wear debris produced by the implant material degradation (Souza et al, 2015).…”
Section: Do Bio-tribocorrosion Products Affect the Peri-implant Tissumentioning
confidence: 99%
“…FIGURE 2 | Gray bars indicate the number of literature reviews published articles with significant discussion of tribocorrosion for restorative dentistry application. The literature reviews reference of each subtopic division are listed as follows: (1) Toh et al, 2018); (2) (Mathew et al, 2014a;Dundon et al, 2017;Espallargas et al, 2017;Villanueva et al, 2017;Cao and Mischler, 2018;López-Ortega et al, 2018;Mombelli et al, 2018; (3) Stack, 2005;Wood, 2007;Wang et al, 2015;Manoj et al, 2019;and, (4) Mathew et al, 2009;Souza et al, 2015;Apaza-Bedoya et al, 2017;Balla and Das, 2017;Revathi et al, 2017;Delgado-Ruiz and Romanos, 2018;Noronha Oliveira et al, 2018). Blue bars indicate the number of tribocorrosion published articles of dental implants and frameworks materials in experimental conditions.…”
Section: The Relevance Of Bio-tribocorrosion In Dentistry and State Omentioning
confidence: 99%
See 1 more Smart Citation
“…They may contribute to the disruption of epithelial barriers, induce oxidative stress and may have cytotoxic and genotoxic potential for tissues. [65][66][67][68] In fact, NAC, as a precursor of GSH, is used as an adjunct to standard therapy for the treatment of chronic obstructive pulmonary disease via improving the neurogenic inflammatory response, a deleterious condition that may support the vicious circle between oxidative stress and inflammation. [69,70] In this study, NAC has been shown to provide a significant protection against titanium toxicity.…”
Section: Clinical Perspectivesmentioning
confidence: 99%